Implementación de un sistema de gestión ambiental de residuos peligrosos en el cantón Pelileo. - Terán Oñate, Rommel Andrés (2023)
The fundamental purpose of the research developed was the Implementation of an Environmental Management System for Hazardous Waste in the Pelileo canton, given the identified problems related to the inadequate disposal of expired or damaged medications considered as hazardous waste, which can cause contamination problems. environmental by bioactive products called contaminants of emerging interest, considered hazardous waste in the canton. To this end, documentary information was collected on how the handling, disposal and management of expired or damaged medications is carried out in homes and pharmacies between 2017 and 2021 in Ecuador, a characterization of the waste generated in the canton was carried out, taking into account The disposal and management of expired or damaged medications in the different pharmacies is taken into account, and on this basis the best environmental practices were identified for the correct management of this waste, with the aim of promoting Environmental Management activities or programs that allow solving the identified problem. . It was found that the population of the canton, in general, throws expired medicines directly into the common garbage, and as a result of this contamination of water, soil and air occurs, so there is no correct differentiated classification of these waste. which can have a harmful influence on the environment. Finally, a strategy was proposed for the final disposal of hazardous waste that contaminates the different urban solid waste collection points in the canton, especially in the area of education of the population, which includes activities such as talks, training, delivery of printed and audiovisual materials, as well as conferences on national and local research.